Process Model Represented in BPMN for Guiding the Implementation of Software Development Practices in Very Small Companies Harmonizing DEVOPS and SCRUM - Pastrana-Pardo, Manuel-Alejandro; Ordoñez-Erazo, Hugo-Armando; Cobos-Lozada, Carlos-Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The business process model is a graphic representation mechanism that helps improve the understanding of a context, the steps undertaken, and the validations and business rules that are part of its universe. This article proposes an implementation model of practices for software development based on DevOps suggestions and how these might be executed within Scrum by the Scrum Development Team (SDT). Present a practice implementation model that integrates DevOps suggestions to be executed by a scrum development team (SDT). The practices for software development based on DevOps were identified. The moment in which the information provided is helpful for the team's continuous improvement within SCRUM was determined. With the practices identified, modeling the general process of implementing practices using BPMN was conducted, followed by detailed modeling. Finally, experts executed the evaluation of the detailed process model. A 12-question survey was implemented to understand the business process model created for implementing practices. This instrument was then made available to experts in the field to obtain feedback on what has been done. The results obtained are promising. The set of practices suggested by DevOps and its integration in Scrum allows for establishing a preventive quality approach for the best development of software products. Using business process models represented by BPMN allows companies to understand and adopt the proposed practices quickly.